2004
DOI: 10.1074/jbc.m404272200
|View full text |Cite
|
Sign up to set email alerts
|

Herp Stabilizes Neuronal Ca2+ Homeostasis and Mitochondrial Function during Endoplasmic Reticulum Stress

Abstract: In response to endoplasmic reticulum (ER) stress, cells launch homeostatic and protective responses, but can also activate cell death cascades. A 54 kDa integral ER membrane protein called Herp was identified as a stress-responsive protein in non-neuronal cells. We report that Herp is present in neurons in the developing and adult brain, and that it is regulated in neurons by ER stress; sublethal levels of ER stress increase Herp levels, whereas higher doses decrease Herp levels and induce apoptosis. The endop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
148
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(161 citation statements)
references
References 60 publications
11
148
0
2
Order By: Relevance
“…CREB3 is produced in large amounts in the CNS (Ying et al, 2014), and Herp has been shown to regulate Ca 2+ homeostasis in neurons and to prevent ER stress-induced apoptosis (Belal et al, 2012;Chan et al, 2004). These findings, together with our results, suggest that the CREB3/ Herp module may be involved in the delicate balance between pro-and anti-apoptotic signals underlying the PVinduced neuropathogenesis of poliomyelitis.…”
Section: Herpsupporting
confidence: 66%
See 2 more Smart Citations
“…CREB3 is produced in large amounts in the CNS (Ying et al, 2014), and Herp has been shown to regulate Ca 2+ homeostasis in neurons and to prevent ER stress-induced apoptosis (Belal et al, 2012;Chan et al, 2004). These findings, together with our results, suggest that the CREB3/ Herp module may be involved in the delicate balance between pro-and anti-apoptotic signals underlying the PVinduced neuropathogenesis of poliomyelitis.…”
Section: Herpsupporting
confidence: 66%
“…CREB3 is a transcription factor associated with ER stress and the ERAD pathway through activation of the Herp gene in particular (Asada et al, 2011;Chan et al, 2011;Liang et al, 2006). Herp plays a key role in ER stress recovery (Yan et al, 2014), and regulates Ca 2+ homeostasis in the ER (Belal et al, 2012;Chan et al, 2004).…”
Section: Herpmentioning
confidence: 99%
See 1 more Smart Citation
“…HERP being a membrane protein, considerable effort was dedicated to identification of a suitable solubilization approach facilitating release of HERP from the ER membrane in a form compatible with its capture via His-tagged p40 on Ni 2ϩ -NTAagarose. Three isolation protocols were tested starting from cells treated with thapsigargin, previously shown to significantly up-regulate HERP (33) (Fig. 3, B and C).…”
Section: Kinetics Of Herp Mrna and Protein Induction By Tfm-c And Optmentioning
confidence: 99%
“…High expression of Herp with formation of amyloid β -protein deposited in vascular cells was observed in the brains of patients with Alzheimer disease (Sai et al 2002). Herp may regulate neuronal Ca 2+ signaling (Chan et al 2004), and the expression of Herp markedly increased in neurons of rats subjected to ER stress (Hori et al 2004). Herp may play a protective role against ER stress.…”
Section: Recombinant Herp Proteinmentioning
confidence: 97%